A revision of the Indo-Pacific fish genus Caragobius (Gobiidae: Amblyopinae) - Murdy, Edward O.; Shibukawa, Koichi (Zootaxa, 2003)
The Indo-West Pacific gobiid genus Caragobius Smith and Seale is revised and defined. Caragobius has been frequently considered a synonym of Brachyamblyopus; however, Caragobius is unique within the Amblyopinae in having: 3–7 (typically 4–6) anal-fin pterygiophores anterior to first hemal spine; fifth hypural absent; and ribs lacking on 3rd precaudal vertebra. Caragobius comprises two species: C. rubristriatus, known from northern Australia, and C. urolepis, known from India, Thailand, Indonesia, the Philippines, Taiwan, Japan, and Fiji. Images of both species are provided. Caragobius is compared to Brachyamblyopus and Trypauchen-Group members.